2002
DOI: 10.1128/jvi.76.11.5588-5597.2002
|View full text |Cite
|
Sign up to set email alerts
|

Increased Production of Interleukin-8 in Primary Human Monocytes and in Human Epithelial and Endothelial Cell Lines after Dengue Virus Challenge

Abstract: The more severe form of dengue virus infection, dengue hemorrhagic fever, is characterized by plasma leakage and derangements in hemostasis. As elevated interleukin-8 (IL-8) levels have been observed in sera from patients with more severe disease manifestations, a study was initiated to look at the effect of dengue virus infection in vitro on proinflammatory cytokine secretion and expression. A significant increase in IL-8 levels in the culture supernatant of primary human monocytes infected with dengue 2 viru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
114
3

Year Published

2003
2003
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(125 citation statements)
references
References 34 publications
8
114
3
Order By: Relevance
“…Dengue viruses can replicate in monocyte-derived macrophages and monocyte-like cell lines (Kurane et al, 1990;O'Sullivan & Killen, 1994) and induce cytokines (Bosch et al, 2002;Espina et al, 2003) and cytotoxic factors (Mukerjee et al, 1995;Shaio et al, 1995). Culture fluids from dengue virus-infected peripheral blood monocytes activated endothelial cells, as measured by upregulation of cell adhesion molecules (Anderson et al, 1997), and increased the permeability of endothelial cells in vitro (Carr et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dengue viruses can replicate in monocyte-derived macrophages and monocyte-like cell lines (Kurane et al, 1990;O'Sullivan & Killen, 1994) and induce cytokines (Bosch et al, 2002;Espina et al, 2003) and cytotoxic factors (Mukerjee et al, 1995;Shaio et al, 1995). Culture fluids from dengue virus-infected peripheral blood monocytes activated endothelial cells, as measured by upregulation of cell adhesion molecules (Anderson et al, 1997), and increased the permeability of endothelial cells in vitro (Carr et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial cells can be infected with dengue virus in vitro (Bunyaratvej et al, 1997;Huang et al, 2003;Killen & O'Sullivan, 1993). Dengue virus infection induces cytokine production (Avirutnan et al, 1998;Bosch et al, 2002) and alters the expression of adhesion molecules on endothelial cells (Krishnamurti et al, 2002). Although endothelial cells are not massively infected, there is evidence of dengue virus infection of endothelial cells in vivo (Gubler & Zaki, 1998;Hall et al, 1991;Jessie et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In these in vitro models it has been shown that the viral E protein binds to the endothelial cell surface in the absence of Fc receptors (Chen et al, 1996) and that infected cells produce high levels of IL8 as well as IL6 (Bosch et al, 2002;Huang et al, 2000). E protein also binds to other cell lines such as Vero, Chinese hamster ovary and glia (Chen et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Virus entry is suspected as viral RNA has been detected in brain microvascular endothelial cells from a fatal case of DHF (Ramos et al, 1998). Interleukin (IL) 8 and other cytokines have been proposed as inducers of alterations in endothelial function, because elevated levels of cytokines have been found in serum and pleural fluid of patients with DHF and in dengue virus-infected human primary monocytes (Raghupathy et al, 1998;Bosch et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation